Life of Klim Samgin as a Novel about the “A Man without Qualities” - Paola Cioni (Studia Litterarum)
Starting from the 1930s, the interpretation of Maxim Gorky’s works has been deeply influenced by the judgements of political kind that determined, especially in the Western world, a considerable decrease in interest towards his works. Furthermore, the identification of Gorky with socialist realism often made critics completely deny his literary talent. Today’s courses of Russian literature do not devote much space to Gorky and his literary works, with rare exceptions, are no longer translated. At this point, it is worth asking oneself if Gorky’s association with socialist realism was true. Many documents published in the last few years show that the writer did not even take part in the meetings which defined new developments in literature and that after the Union of writers had been created, he did not agree with the way it was organized. Besides, the late works by Gorky, starting from Short Stories of the 1922–1924 and ending with Life of Klim Samgin, as it has been argued by Mark Slonim in 1953, have nothing in common with socialist realism. The goal of this article is to give a different interpretation of Gorky’s last novel and to place it back into the context of European modernism, through both the thematic analysis of Life of Klim Samgin and the statements of the writer himself. In fact, while reading the writer’s last works it becomes clear that Gorky never wrote a single line in the spirit of Socialist Realism.